(untitled) - Jacob, Jérôme; Pino-Herrera, Douglas; Greffié, Catherine; Wille, Guillaume; Plat, Emmanuelle (Comptes Rendus. Chimie)
Acid mine drainages (AMDs) are a major environmental problem, but they can also contain valuable metals. A typical treatment of AMDs consists in the neutralization and precipitation of metals by liming, which produces a sludge mainly composed of iron oxyhydroxides and gypsum. Depending on the AMD composition, the sludge can contain important concentrations of valuable metals. This research work aimed at studying acid leaching of copper and zinc present in the sludge with the final goal of developing a process to recover these metals. Tests were carried out using sludge from a former mining site in France. The first stage of this process involves a leaching stage to selectively dissolve Cu, Zn, and Cd using H2SO4. This process allows more than 80% of Cu and Zn as well as 98% of Cd in the sludge to be leached under optimal operating conditions, which are between 5% and 15% of solid content and between 150 and 200 g H2SO4·kg–1 at room temperature. Using more acid marginally increases the dissolution rates but at the cost of much higher acid consumption linked to the dissolution of iron and therefore a loss of selectivity.